2000
DOI: 10.2174/1381612003399419
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Synthetic Endocannabinoids and Their Structure-Activity Relationships

Abstract: During the past several years, cannabinoid biology has witnessed marked advances that has propelled it to the forefront of biomedical research. These new developments have also provided an opportunity to examine the physiological and biochemical events underlying the use and abuse of cannabis as well as elucidating the biological role of the endogenous cannabinoid ligands (endocannabinoids). The biological targets for endocannabinoids include the cannabinoid receptors (CB1 and CB2), the enzyme anandamide amido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 75 publications
0
29
0
Order By: Relevance
“…The two most studied cannabinoid receptors, CB1 and CB2, have different binding affinities for AEA and its metabolites. CB1 is found in the brain and in other tissues (Palmer et al, 2000;Kozak and Marnett, 2002;Snider et al, 2009) and has been demonstrated to be involved in the cannabinoid signaling pathway that protects against stroke in mice (Parmentier- Batteur et al, 2002;Marsicano et al, 2003;Panikashvili et al, 2005). The second receptor, CB2, is involved in inflammation, and agonists targeting CB2 are currently being developed as therapies to reduce inflammation and pain (Whiteside et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The two most studied cannabinoid receptors, CB1 and CB2, have different binding affinities for AEA and its metabolites. CB1 is found in the brain and in other tissues (Palmer et al, 2000;Kozak and Marnett, 2002;Snider et al, 2009) and has been demonstrated to be involved in the cannabinoid signaling pathway that protects against stroke in mice (Parmentier- Batteur et al, 2002;Marsicano et al, 2003;Panikashvili et al, 2005). The second receptor, CB2, is involved in inflammation, and agonists targeting CB2 are currently being developed as therapies to reduce inflammation and pain (Whiteside et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the ECs are synthesized in the postsynaptic neurons and are released into the synaptic cleft, where they act as retrograde messengers [14]. They are removed rapidly from the extracellular space through uptake and catabolism [17,[32][33][34]. In the CNS, the ECs activate CB1 receptors and regulate synaptic transmission of both excitatory and inhibitory circuits by modulating the release of monoamine neurotransmitters [9,14].…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%
“…In a very early SAR finding, the importance of the side chain was first demonstrated by Adams (Adams, 1942;Adams et al, 1949) where the 1V,1V-dimethylheptyl analogue was shown to be 100-fold more potent than the n-hexyl analogue in the D 6a,10a -THC series. Subsequent SAR studies on classical cannabinoids (CCs) have recognized the C-3 alkyl side chain as the most critical pharmacophoric group (Howlett et al, 2002;Khanolkar et al, 2000;Makriyannis and Rapaka, 1990;Palmer et al, 2000Palmer et al, , 2002Thakur et al, 2005a). Therefore, the focus of this review of the SAR studies of analogues derived from cannabinoids and endocannabinoids is on the terminal n-pentyl tail.…”
Section: Side Chain Sar Of Cannabinoids and Endocannabinoidsmentioning
confidence: 99%
“…This is substantiated by structure -activity relationship (SAR) work which revealed a number of similarities between the two classes of cannabinergics. The SAR studies performed on classical cannabinoids represented by D 9 -THC (2) and its next generation analogues, the non-classical (Johnson and Melvin, 1986;Little et al, 1988) and hybrid cannabinoids (Chu et al, 2003;Drake et al, 1998;Harrington et al, 2000;Makriyannis and Rapaka, 1990;Thakur et al, 2002;Tius et al, 1997Tius et al, , 1994, have recognized four pharmacophores within the cannabinoid prototype: a phenolic hydroxyl (PH), a lipophilic side chain (SC), a northern aliphatic hydroxyl (NAH), and a southern aliphatic hydroxyl (SAH) (for reviews see: Howlett et al, 2002;Khanolkar et al, 2000;Makriyannis and Rapaka, 1990;Palmer et al, 2000Palmer et al, , 2002Thakur et al, 2005a,b). This review focuses on the SAR of the ''lipophilic side chain,'' the key pharmacophore which plays a crucial role in determining ligand affinity and selectivity towards cannabinoid receptors as well as pharmacological potency.…”
Section: Introductionmentioning
confidence: 99%